Aplicação da programação linear em problemas agrícolas - Reghim, Daniely Cristiny Lucas (2018)
Currently, the agroindustrial sectors have been seeking the improvement and the technological knowledge of their expertise areas, due to the strong competition in the market. This fact motivates the development of actions that optimize processes, such as to produce food avoiding waste of raw materials and inputs, or preserve the environment, by increasing the planted area. Agricultural production, in its turn, has adapted old practices to more current production technologies with the goal of increasing productivity, cultivating healthier products and reducing environmental impacts. Thus, the goal of this work is to formulate problems using linear programming in agricultural problems. The presented case studies involve the maximization of profits of an agricultural production and of a reforestation property. Linear programming problems were solved with computational support in order to obtain the solutions by running the SIMPLEX method, providing efficiency in the planning of cultures rotation in agricultural properties.